Cost effectiveness of peginterferon α-2b plus ribavirin versus interferon α-2b plus ribavirin for initial treatment of chronic hepatitis C. Issue 3 (1st March 2003) - Siebert, U; Sroczynski, G; Rossol, S; Wasem, J; Ravens-Sieberer, U; Kurth, B M; Manns, M P; McHutchison, J G; Wong, J B
Abstract : Background: Peginterferon α-2b plus ribavirin therapy in previously untreated patients with chronic hepatitis C yields the highest sustained virological response rates of any treatment strategy but is expensive. Aims: To estimate the cost effectiveness of treatment with peginterferon α-2b plus ribavirin compared with interferon α-2b plus ribavirin for initial treatment of patients with chronic hepatitis C. Methods: Individual patient level data from a randomised clinical trial with peginterferon plus ribavirin were applied to a previously published and validated Markov model to project lifelong clinical outcomes. Quality of life and economic estimates were based on German patient data. We used a societal perspective and applied a 3% annual discount rate. Results: Compared with no antiviral therapy, peginterferon plus fixed or weight based dosing of ribavirin increased life expectancy by 4.2 and 4.7 years, respectively. Compared with standard interferon α-2b plus ribavirin, peginterferon plus fixed or weight based dosing of ribavirin increased life expectancy by 0.5 and by 1.0 years with incremental cost effectiveness ratios of 11 800 and 6600 per quality adjusted life year (QALY), respectively. Subgroup analyses by genotype, viral load, sex, and histology showed that peginterferon plus weight based ribavirin remained cost effective compared with other well accepted medical treatments. Conclusions: Peginterferon α-2b plus ribavirin should reduce the incidence of liver complications, prolong life, improve quality of life, and be cost effective for the initial treatment of chronic hepatitis C.